Economic woman : demand, gender, and narrative closure in Eliot and Hardy - Kreisel, Deanna K. (Toronto [Ont.] : University of Toronto Press, 2012)
"The ways in which women are portrayed in Victorian novels can provide important insights into how people of the day thought about political economy, and vice versa. In Economic Woman, Deanna K. Kreisel innovatively shows how images of feminized sexuality in novels by George Eliot and Thomas Hardy reflected widespread contemporary anxieties about the growth of capitalism.
Economic Woman is the first book to address directly the links between classical political economy and gender in the novel. Examining key works by Eliot and Hardy, including The Mill on the Floss and Tess of the d'Urbervilles, Kreisel investigates the meaning of two female representations: the "economic woman" who embodies idealized sexual restraint and wise domestic management, and the degraded prostitute, characterized by sexual excess and economic turmoil. Kreisel effectively integrates economic thought with literary analysis to contribute to an ongoing and lively scholarly discussion."--Pub. desc.
Popular demand: surplus and stagnation in nineteenth-century political economy -- 'Fine clothes an' waste': utopian economy and the problem of femininity in Adam Bede -- Superfluity and suction: the problem with saving in The Mill on the Floss -- 'All was over at last': epistemological and domestic economies in The Mayor of Casterbridge -- Self-sacrifice, skillentons, and mother's mild: the internationalization of demand in Tess.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Eliot, George, -- 1819-1880 -- Knowledge -- Economics; Hardy, Thomas, -- 1840-1928 -- Knowledge -- Economics; Eliot, George, -- 1819-1880; Hardy, Thomas, -- 1840-1928; English fiction -- 19th century -- History and criticism; Economics and literature -- Great Britain -- History -- 19th century; Women in literature; Economics in literature; Roman anglais -- 19e siècle -- Histoire et critique; Économie politique et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes dans la littérature.; Économie politique dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- General; Economics; Economics and literature; Economics in literature; English fiction; Women in literature; Great Britain; 1800-1899; Criticism, interpretation, etc; History